A study on the factors that contribute to bullying in girls cluster schools in Malacca / Fairul Haziq Mohd Aris and Nor Fadila Md Yasin - Mohd Aris, Fairul Haziq; Md Yasin, Nor Fadila (Faculty of Administrative Science and Policy Studies, 2013)
Bullying cases are serious problems that occurring among teenagers. It contributes to the raising juvenile cases which eventually influence the teenagers to do criminal behavior when they are grown up. They are many definitions that are said as bullying. Because of that, some definitions are given to support the meaning of bullying for the purpose of the research. Bullying is the repeated and ongoing negative action toward one or more students (Olweus, 1993). These negative actions can be direct, as in verbal or physical contact, facial or other body gestures, or indirect, as in the intentional exclusion or refusal to comply with another person’s wishes (Rigby, 2002). Hence, bullying may be simply defined as the act of constant aggression toward another individual who lacks the same power. Most of the crimes in the school begin with the problem of bullying. The seriousness of the problem of bullying among school children should be dealt with immediately. If not, it might be a big problem for the country in the future. In order to do that, the causes of the bullying cases have to be determined first. This is what the purpose of the research is carried out. There are some factors that are of concern by the researchers which are individual factors, environmental factors and social factors. Individual factors are more concern on the personality and traits of the bully and victims. Environmental factors emphasized by the researchers are mass media and also the electronic devices. Social factors concern on the involvement of parents and also the influence of friends. The researchers believe that these three factors have relation with bullying. Correlation between the factors and bully is found out and the most determinant factor is figured out in order to give some recommendations to ensure the bullying can be reduced.